Comparative study on the critical current density of MgB2 prepared by mixed boron powders - Chen, Soo Kien; Lim, Kean Pah; Tan, Kar Ban; Shaari, Abdul Halim (Malaysian Solid State Science and Technology Society, 2009)
Polycrystalline MgB2 was prepared from Mg and boron precursors consisting of boron powders with varying purity and form. Tc does not change largely for all samples. By replacing 10 wt.% of high purity amorphous boron with impure crystalline boron, comparable Jc to that of samples prepared from high purity amorphous boron powder alone can be obtained. High Jc can also be retained by replacing 20 wt.% of the high purity amorphous boron with impure amorphous boron. However, Jc decreases more rapidly with field by increasing the proportion of impure amorphous boron. By mixing both impure amorphous and crystalline boron powders even up to the proportion of 50 ¨C 50 wt.%, the obtained MgB2 exhibit enhanced Jc compared to samples prepared from the respective boron powder alone. The enhancement in Jc at 6K and 20K is more pronounced for applied field ≤ 3T.